What is the key to culturally competent care: Reducing bias or cultural tailoring?. Issue 4 (3rd April 2017) - Cuevas, Adolfo G.; O'Brien, Kerth; Saha, Somnath
Abstract : Objective: To gain a better understanding as to whether disparities in patient–provider relationships arise from ethnic minority patients being treated differently than European American patients while they would prefer to be treated the same, or whether disparities arise when ethnic minority patients are treated the same as European American patients while they would prefer to be treated differently. Method: African-American, Latina/Latino and European American community members were recruited to participate in one of 27 focus group discussions. Topics included what made a good or bad relationship with a doctor and what led one to trust a doctor. A thematic analysis was conducted using NVivo 10. Results: Patients of all groups described experiences that reflected the concepts of patient-centred care, such as wanting a clinician who is attentive to patients' needs. African-American patients reported experiences they viewed as discriminatory. Some African-American patients felt it was appropriate to racially/ethnically contextualise their care, and most Latina/Latino patients preferred language/culturally concordant clinicians. Conclusion: Health care disparities might be reduced through a patient-centred approach to cultural competency training, general knowledge of the cultural context of clinicians' patient population, and attention to the effects of racial bias and discrimination among both clinicians and non-clinical staff.